Does the Chinese version of 20-item Toronto alexithymia scale (TAS-20-C) measure alexithymia in Chinese young adolescents? Evidence from confirmatory factor analysis, network analysis, and latent profile analysis - Yuhan Ni; Shuanghu Fang (BMC Psychology)
Abstract The 20-item Toronto Alexithymia Scale (TAS-20) is a measure of three components of alexithymia: difficulty identifying feelings (DIF), difficulty describing feelings (DDF), and externally oriented thinking (EOT). Although TAS-20 is being increasingly used to measure the alexithymia construct, ongoing controversies remain regarding its internal structure and cross-cultural and cross-group applicability. This study evaluated the psychometric properties of the Chinese version of TAS-20 (TAS-20-C) among 1,355 Chinese young adolescents (mean age = 13.13; SD = 1.00; 52.6% boys) through multiple analytic approaches (i.e., confirmatory factor analysis, network analysis, and latent profile analysis). The confirmatory factor analysis showed reasonable goodness-of-fit for the bi-factorial model with three-dimensional structure and a negatively keyed item factor. However, the results derived from all analytic approaches suggested several items with poor psychometric properties (items 5, 10, 16, 18, 19, 20 from EOT and item 12 from DDF), including poor factor loading on their intended factor, low connectivity and predictability in the item network, and insufficient discrimination across heterogeneous groups. These issues could be attributed to an overabundance of negatively keyed items, translation biases, and the poor readability of certain items. The findings highlight the need for targeted revisions to both the wording and the content for these items, and offer insights into higher priority interventions aimed at improving alexithymia.